P‐44: Polysulfide Elastomers as Highly Elastic Materials for Flexible Displays. Issue 1 (25th September 2020) - Vega, Abraham; Yang, Kejia; Reit, Radu
Abstract : In this study, we will discuss the design of polysulfide thermosets (PSTs) with elastomeric properties, namely low Young's modulus (< 10 MPa), high elastic strains to failure (> 25%) and other challenging properties needed for the new dynamic form‐factor displays. We focus specifically on the elastic requirements of these low‐modulus materials and the need for a lack of irreversible strain after multiple cycles of loading and unloading. These PST materials yield films with low hysteretic behavior (<8% in the highest‐strain compositions vs. >35% for standard OCA films) and virtually no irreversible strain after cyclic loading (<1% in all compositions vs. >30% in current commercial alternatives). These results show the promise that PST materials will to satisfy the challenging mechanical needs of deformable displays and discuss how future elastomeric research and development should aim to address these challenges.